Border building and breaking practices on the Turkish-Syrian border - Kıyanç, Yakup. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
This study aims to analyze border building and breaking practices at the Turkish- Syrian border in the context of the Mür itpınar-Kobanê border region. After the first chapter of this study, which explains the border theory and terminology in detail, the second chapter deals with border building practices –chronologically boundary stones, barbed wire, landmines, watch towers, border gates, and the wall with its most recent form- carried out by the state from the early Republican era to this day. Besides, in this chapter, I have benefited from the Separation Wall in Palestine as one of the similar cases around the world. The last chapter focuses on border breaking practices of people of the border region as opposed to border building practices of the state. After an analysis of cross-border economic, cultural, and political relations maintained by people of the border region despite the border, the chapter introduces the smuggling and political resistance in detail as border breaking practices. My main argument based on the field research in and observations from the region is that border building practices of the Turkish State aim to cut the communication between the Kurds in the region (Turkey and Syria). I raise this argument by concentrating on the wall the Turkish State has started to build after the Syrian civil war.
Keywords: Border security -- Turkey.; Border security -- Syrian.; Emigration and immigration -- Government policy.; Boundaries.; Knitted wall